Reconfigurable microstrip array antenna - Chin, Liang Nan (Universiti Sains Malaysia, 2013)
This project presents a frequency tunable microstrip array antenna as the number of radiating element changes. Operating bandwidth and gain are also reconfigured with the change in number of array elements. All designs in simulation stage are carried out using CST 2008. At first, the design start with single element antenna, followed by 1x2 array antenna configuration, finally proceed to 1x4 array antenna configuration. Different feeding techniques are used in single element antenna design to find out suitable feeding method for this design. After that, corporate feeding network is used in array antenna design as this feeding network can ensure all signal can reach every antenna patch at same magnitude and phase since their feed line length are same. Quarter-wave transformers are used to make sure impedance is matched at all feed line junction. One of the major concerns when designing array network is the discontinuities that happened at every right angle bends, T junctions and step changes in line width, discontinuities will introduce parasitic reactances that may lead to phase and amplitude error. In order to reduce this problem, some compensation techniques such as mitered bend and curved bend have been carried out. In this project, all antenna designs have been fully optimized by finding suitable feed point in simulation stage. All design are fabricated and deployed on FR-4 with thickness of 1.6mm, dielectric constant of 4.5 and loss tangent of 0.021. Measurement results show that as number of resonator increases from one element to four elements, the prototype of proposed antenna can cover frequency range from frequency 2.515 GHz to 2.53 GHz. At the same time, antenna gain will increase from 1.799 dB to 5.8 dB and bandwidth will increase from 91.1 MHz to 120 MHz. The percentage of difference of simulated and measured resonant frequency is small, which is around 5-7% for all antenna designs.